2017
DOI: 10.2903/j.efsa.2017.4855
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Bacillus subtilis PB6 (Bacillus subtilis ATCC PTA‐6737) as a feed additive for sows

Abstract: Bacillus subtilis PB6 is a feed additive based on viable spores of a strain of Bacillus subtilis. EFSA has already issued several opinions on the safety and efficacy of the additive when used in the feed for a number of avian and porcine species/categories. The applicant is now seeking authorisation for use in sows in order to have benefits in piglets. In the course of previous assessments, no evidence of a toxigenic potential or resistance to relevant antibiotics was found. Consequently, the strain of B. subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The increased NBA in the treatment group was in agreement with some previous findings [ 5 , 8 , 9 ]. However, many other studies reported nonsignificant effect of probiotic supplementation on this criterion [ 4 , 6 , 7 , 10 , 14 20 ]. The positive effect of the probiotic supplementation on NBA may be partly attributable to the fact that it reduced stillbirth rate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increased NBA in the treatment group was in agreement with some previous findings [ 5 , 8 , 9 ]. However, many other studies reported nonsignificant effect of probiotic supplementation on this criterion [ 4 , 6 , 7 , 10 , 14 20 ]. The positive effect of the probiotic supplementation on NBA may be partly attributable to the fact that it reduced stillbirth rate.…”
Section: Discussionmentioning
confidence: 98%
“…It is interesting that Bacillus subtilis QST 713 increased both litter size/NBA and birth weight despite the fact that birth weight is negatively associated with litter size [ 25 , 26 ]. Some previous studies failed to find any beneficial effects of probiotic supplementation at late gestation on birth weight of piglets [ 7 9 , 20 ] while other studies even found a reduced birth weight in the probiotic supplementation group where litter and/or NBA increased in comparison with that in the control [ 5 , 14 ]. Two previous studies found that birth weight was increased while litter sizes were unaltered when probiotic was supplemented throughout 2 successive estrus cycles [ 27 ] or late gestation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the present dossier, the applicant states that no adverse events have been reported since the market authorisation of the additive (2013). 28 In the previous assessments (EFSA FEEDAP Panel, 2012a, 2013, 2017a, 2020, the active agent B. velezensis ATCC PTA-6737 was presumed safe for the target species, consumers and the environment based on the qualified presumption of safety (QPS) approach (EFSA, 2007;EFSA BIOHAZ Panel, 2023).…”
Section: Safetymentioning
confidence: 99%
“…EFSA has issued several opinions on the safety and efficacy of Bacillus velezensis 3 ATCC PTA‐6737 ( Bacillus subtilis PB6) as a feed additive for different species: chickens for fattening (EFSA FEEDAP Panel, 2009 ), chickens reared for laying, ducks for fattening, quails, pheasants, partridges, guinea fowl, pigeons, geese for fattening and ostriches (EFSA FEEDAP Panel, 2011 ), weaned piglets and weaned minor porcine species (EFSA FEEDAP Panel, 2012a ), turkeys for fattening and turkeys reared for breeding (EFSA FEEDAP Panel, 2013 ), laying hens, other minor laying poultry birds (EFSA FEEDAP Panel, 2015 ) and sows (EFSA FEEDAP Panel, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous assessments (EFSA FEEDAP Panel, 2012, 2013, 2017a, PB6 (B. velezensis PTA-6737) was presumed safe for the target species, consumers and the environment based on the qualified presumption of safety (QPS) approach. In a recent opinion (EFSA FEEDAP Panel, 2020) and in the current assessment, the active agent has been reclassified as B. velezensis and its taxonomical identity and its compliance with the QPS qualifications confirmed.…”
Section: Safety and Efficacymentioning
confidence: 99%